Structural, electrical and optical investigations of Cu₆PS₅Br-based thin film deposited by HiTUS technique - Studenyak, I.P.; Kutsyk, M.M.; Studenyak, V.I.; Bendak, A.V.; Izai, V.Yu.; Kúš, P.; Mikula, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Cu₆.₃₅P₁.₇₇S₄.₇₂Br₀.₁₅ thin film was obtained using the high target utilization sputtering onto c-cut sapphire substrates. X-ray diffraction studies show the film to be amorphous with some crystalline inclusions. SEM investigations indicate formation of periodical “forest-like” quasi-two-dimensional pillared structure. Electrical conductivity of Cu₆.₃₅P₁.₇₇S₄.₇₂Br₀.₁₅ thin film was measured in the temperature interval 4.5…300 K, three regions with different activation energy were revealed. Optical constants were obtained using the technique of spectroscopic ellipsometry and used for calculation of optical absorption spectrum. Optical absorption edge has an exponential form, the Urbach energy shows the significant disordering in Cu₆.₃₅P₁.₇₇S₄.₇₂Br₀.₁₅ thin film.